SYNTHESIS AND CHARACTERIZATION OF CHITOSAN NANOPARTICLES CONTAINING MANGOSTIN AND PROPOLIS AS DRUG DELIVERY SYSTEM - RAHMAWATI (NIM : 21115020), RESMI
Mangostin is an organic compound which isolated from mangosteen pericarp and propolis is a substances which collected by bee from tree sap for fixing and guarding bee hive. Both of these biomolecules has a role as anticancer agent. In previous studies the combination of mangostin and propolis could increase the effectiveness of anticancer in inhibiting the development of mammary cancer in mice. Therefore both of these biomolecules are potential for cancer treatment. The aim of this research is to encapsulate mangostin and propolis in chitosan nanoparticles in order to created an effective drug delivery system and to characterize the nanoparticles. Chitosan nanoparticles are synthesized by ionic gelation method using polyanionic cross-linker i.e. sodium tripolyphosphate (TPP). Combination of chitosan concentration and sonication treatment was used to obtain the smallest nanoparticles diameter. Mean nanoparticles diameter, polydispersity index, and zeta potential were measured using zetasizer (Malvern). Morphology of chitosan nanoparticles was analyzed using Scanning Electron Microscopy (SEM). Chitosan nanoparticles with the smallest mean diameter were then analyzed with Fourier Transform InfraRed spectrophotometer (FTIR). Chitosan nanoparticles was added containing mangostin and propolis and synthesized by the same method. Before lyophilization the nanoparticles solution was added trehalose as cryo-protectant. Nanoparticles analyzed using Transmission Electron Microscopy (TEM). The results showed the smallest nanoparticle diameter was obtained from 0,075% chitosan concentration and 0,025% TPP concentration. The size that the nanoparticle has after sonication was 245,4 nm. FTIR have been confirmed TPP linked with ammonium groups of chitosan, the peak was 1261.4 1/cm. Chitosan nanoparticles showed spherical morphology analyzed with SEM. Four nanoparticles successfully synthesized i.e. NP-Blanko, NP-M, NP-P and NP-Dual. The size, PdI and zeta potential from that nanoparticles were consecutively NP-Blanko: 198,2 nm; 0,197 and +46,9 mV, NP-M: 220,3 nm; 0,248 and +50,9 mV, NP-P: 261 nm; 0,249 and +34,6 mV, and NP-Dual: 265,4 nm; 0,343 and +56,9 mV. In conclusion nanoparticle has increased in size as the addition of drugs. TEM of the nanoparticles are showed spherical shape. This research concluded that chitosan nanoparticles were successfully synthesized by ionic gelation method with the smallest nanoparticle diameter was obtained from 0,075% chitosan and 0,025% TPP. The mean diameter of nanoparticles NP-Blanko; NP-M; NP-P; and NP-Dual were consecutively 198,2 nm; 220,3 nm; 261 nm; and 265,4 nm. Zeta potensial of nanoparticles NP-Blanko; NP-M; NP-P; and NP-Dual were consecutively +46,9 mV; +50,9 mV; +34,6 mV; and +56,9 mV. The shape of nanoparticles were spherical.